Evidence-based HRM through analytics: Reducing the propensity of HRM to become a Cinderella - Cassar, Vincent; Bezzina, Frank (Management Sciences, 2017)
HRM practitioners often struggle to adopt a strategic function in their organization. Borrowing from evidence-based management, this paper highlights the importance of data for enabling better HRM decision-making as irregular decision-making processes can lead to mistakes. Often managers lack the time to evaluate the data and/or have incomplete data. Unfortunately, studies indicate that HRM practices are still heavily based on popular knowledge, misconceptions and behavioural/strategic assumptions of ‘what should work best’. Yet increasingly literature concedes that HRM practices impact performance and the relationship is by and large universal, thus demanding improved decisions through the relevant use of data which has been discussed for many years. The paper addresses important points in HRM analytics and emphasises that this requires HR practitioners to develop three important skill sets: an understanding of data treatment and analysis, the use of IT and knowledge of other business areas since like other fields of management, HRM is evolving and needs to adapt to changes at work to become more strategically relevant
Nauki o Zarządzaniu = Management Sciences, 2017, Nr 4 (33), s. 3-10
Keywords: HRM practitioners; decision making; HRM metrics; HRM analytics; data; evidence-based HRM; praktycy HRM; pomiary HRM; analityka HRM; podejmowanie decyzji; dane; HRM oparte na faktach